(untitled) (Bangladesh Journal of Pharmacology, 2016)
In the present study various solvent extracts from the leaves of Fernandoa adenophylla were screened for their phytochemical and antimicrobial potentials. Preliminary phytochemical screening of leaves extracts showed the presence of alkaloids, glycosides, flavonoids, terpenoids, tannins, steroids, reducing sugars and anthracenes. Fourier transform infrared spectroscopic studies showed the presence of different functional groups for compounds like alcohol, aldehydes and ketones, saturated and unsaturated hydrocarbons, amides, amines, carboxylic acids, esters, and ethers. All the extracts showed significant antibacterial activities when tested against eight multidrug resistant bacterial strains isolated from urinary tract infection patients. It was concluded that the leaves extracts of F. adenophylla have several vital phytochemical constituents and significant antibacterial activities against multidrug resistant bacterial strains causing urinary tract infections.